Development of an Eye Health Literacy Module to Prevent the Negative Impacts of Gadget Use among Elementary School Students - Tasrif; Arifuddin (Postgraduate, University of Mataram, 2026)
This study aims to develop and evaluate an eye health literacy module based on the ADDIE model and a Problem-Based Learning (PBL) approach to strengthen elementary school students’ understanding of the negative impacts of gadget use. The research employed a research and development (R&D) design consisting of needs analysis, design, expert validation, implementation, and evaluation. A total of 72 students participated, selected purposively based on their high daily exposure to digital devices. The instruments, namely, an eye health literacy test and expert validation sheets were reviewed by specialists in education, health, and instructional media. Validation results yielded an average score of 87.6%, categorized as highly feasible. The effectiveness test demonstrated a significant improvement in literacy scores, increasing from 61.4 (pre-test) to 83.7 (post-test) (t = 9.84; p < 0.001). Indicator-based analysis showed consistent enhancement across basic eye-health knowledge, awareness of gadget-related risks, eye-care habits, preventive strategies, and positive health attitudes. These findings confirm that the module not only strengthens conceptual understanding but also fosters preventive behavioral change. The novelty of this study lies in integrating PBL with eye-health literacy materials tailored to students’ digital routines, offering a contextual, interactive, and practice-oriented learning resource. Thus, this module is feasible, practical, and effective as an innovative educational medium and a preventive strategy to mitigate visual health risks associated with prolonged gadget use among elementary school students.